1976
DOI: 10.1056/nejm197606032942304
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and Endometrial Cancer in a Retirement Community

Abstract: All cases of endometrial cancer occurring among the residents of an affluent retirement community were compared with controls chosen from a roster of all women in the same community. Evidence of estrogen and other drug use and of selected medical conditions was obtained from three sources: medical records of the principal care facility, interviews, and the records of the local pharmacy. The risk ratio for any estrogen use was estimated from all available evidence to be 8.0 (95 per cent confidence interval, 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
7

Year Published

1977
1977
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(120 citation statements)
references
References 12 publications
7
103
0
7
Order By: Relevance
“…The risk remains substantially elevated even after 15 years since cessation of use. Other reports have shown that the elevated risk persists after cessation of oestrogen use (Mack et al, 1976;Weiss et al, 1979;Shapiro et al, 1985), but this study extends the risk to longer drug-free intervals. One previous study suggested that the risk of endometrial cancer abates rapidly within two years since cessation of use (Hulka et al, 1980), but most oestrogen use in that study was of short duration (<3 years).…”
Section: Resultssupporting
confidence: 42%
See 2 more Smart Citations
“…The risk remains substantially elevated even after 15 years since cessation of use. Other reports have shown that the elevated risk persists after cessation of oestrogen use (Mack et al, 1976;Weiss et al, 1979;Shapiro et al, 1985), but this study extends the risk to longer drug-free intervals. One previous study suggested that the risk of endometrial cancer abates rapidly within two years since cessation of use (Hulka et al, 1980), but most oestrogen use in that study was of short duration (<3 years).…”
Section: Resultssupporting
confidence: 42%
“…Discussion While our data on both oestrogen use and other variables are self-reported, we have evidence that these data are both reliable and valid (Paganini-Hill & Ross, 1982). Previous studies of oestrogen use in this community have found extremely good correlation in relative risks for various chronic diseases when oestrogen use was ascertained by interviews, medical records or pharmacy records (Mack et al, 1976;Ross et al, 1980;Paganini-Hill et al, 1981).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…NAFEO Conference Scheduled for March [20][21][22]1981 The National Association for Equal Opportunity in Higher Education (NAFEO) will convene its Sixth National Conference on Blacks in Higher Education on March [20][21][22]1981 …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Especially, it has been reported that such EDCs may play an important role in developing uterine adenocarcinoma [1][2][3] that is one of the most common malignant tumors in women 4 . Natural and synthetic estrogens have been shown to express their biological effects mainly by binding to estrogen receptors, and have been found to be major etiological agents for uterine carcinogenesis in humans 5,6 .…”
Section: Introductionmentioning
confidence: 99%